Impact of Islamic Financial Literacy on savings on investment Decisions: The Individual Attitude effect - Atif, Hussain; Asri, Marsidi; Rossazana Ab-Rahim, Ab-Rahim (Atif Hussain, 2024)
This research offers several appealing features for an analysis of Islamic financial Literacy and personal financial management. Individual attitudes intention and behavior are added as the moderating variable on that association. This study explores the re relationship between individual attitude intention and behavior and personal financial management from an empirical perspective. Specifically, by conducting a survey in Sarawak, this research analyses the influence of individual attitude intention and behavior on personal financial management at the individual level focusing on the demographic profiles and financial literacy level. Individual attitudes are classified into individual behavior and intention of the respondents toward Islamic financial literacy and management of the personal financing’ openness to experience, Islamic financial literacy exert relatively large influences on personal financial management in terms of the levels of Islamic financial literacy held by everyone. In contrast, openness to experience and agreeableness appear to be unimportant in influencing personal financial management. The findings also suggest that Individual attitude have different moderating effect with Islamic financial Literacy. while individual is found to have positive moderating effect with Islamic financial Literacy towards personal financial management.